(untitled) (Salud, Arte y Cuidado, 2023)
The objective of this study was to determine the limitations for breastfeeding of the preterm newborn hospitalized in the Dr. Francisco Finizola Intensive Care Unit, Decentralized Service of the Agustín Zubillaga Pediatric University Hospital, in the city of Barquisimeto, Lara State, Venezuela. Methodology: a quantitative approach was used, descriptive type, field design, non-experimental, cross-sectional, the population was 10 mothers with preterm newborns admitted to the NICU. Results: All the newborns included were preterm, 80% were products of mothers who attended less than 7 controls, with UTI, predominantly female, with a range of maximum 7 days of hospital stay, receiving exclusive breastfeeding at through orogastric tube, mothers with little knowledge of the benefits of EBF, milk extraction and conservation. It is concluded that the health status of the preterm newborn and the mother’s lack of knowledge regarding the benefits, practices, extraction and conservation of breastfeeding are limits to effective exclusive breastfeeding in the population studied